The Bible - Prickett, Stephen 1939-2020 (Cambridge University Press, 1991)
This study focuses on the Bible as a landmark of literature, showing both how it has influenced writers through the ages and how it in turn has been influenced by contemporary literature. It describes what is known about the historical context of the documents, the changes of interpretation they have undergone over the centuries, and the problems and influence of various translations, ranging from Tyndale to the Good News Bible
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible / Introductions; Bibel